2022
DOI: 10.7595/management.fon.2022.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Brand Personality Concept on Consumer Satisfaction and Loyalty

Abstract: Research Question: The goal of this research is to describe how the concept of brand personality and its dimensions affect customer satisfaction and loyalty. Motivation: Creating brand personality is an efficient differentiation strategy, used by numerous companies for building and sustaining competitive advantage. Brands with personality are considered as real people and can be described using human characteristics. Therefore, consumers can establish connection with them more easily, which increases customer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, Tsao and Chang found out consumer personality is a powerful predictor of consumer satisfaction, and the connection between consumer personality and brands leads to an increase in consumer satisfaction, which indicates that people with certain personalities would be more likely to feel satisfied with a brand [17]. Further on, Marković has found that brand personality (sincerity, excitement, competence, sophistication, and strength) has a significant positive affect consumer satisfaction [18]. Hence, the second and third hypothesis are developed as follows:…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…For example, Tsao and Chang found out consumer personality is a powerful predictor of consumer satisfaction, and the connection between consumer personality and brands leads to an increase in consumer satisfaction, which indicates that people with certain personalities would be more likely to feel satisfied with a brand [17]. Further on, Marković has found that brand personality (sincerity, excitement, competence, sophistication, and strength) has a significant positive affect consumer satisfaction [18]. Hence, the second and third hypothesis are developed as follows:…”
Section: Hypotheses Developmentmentioning
confidence: 99%